Sound of silence : a festschrift in honour of Bishop Dhirendra Kumar Sahu at his shashti-purti - Sahu, Dhirendra Kumar; Tiwari, Ravi, 1948-; Sahu, Bibhudutta; I.S.P.C.K. (Organization) (Delhi : ISPCK, 2010)
Contributed articles.
Includes bibliographical references.
Keywords: Sahu, Dhirendra Kumar; Theology -- India; Spiritual life -- Christianity